A New Name for an Overlooked Species of Eulophia (Orchidaceae) from Wallacea - Metusala, Destario (Phytotaxa, 2019)
Eulophia bicolor described by Blume is an illegitimate name for a species that has generally been considered synonymous with E. nuda. The former should be recognized as a distinct species, as it differs in having different spur characteristics, a narrower column, and an anther cap with an elongated protuberance. It is here given a new name, E. lagaligo.